2021
DOI: 10.3390/ma14154289
|View full text |Cite
|
Sign up to set email alerts
|

Surface Treatment of Zn-Mn-Mg Alloys by Micro-Arc Oxidation in Silicate-Based Solutions with Different NaF Concentrations

Abstract: Newly developed Zn-Mn-Mg alloys can be invoked as biomedical materials because of their excellent mechanical properties. However, the corrosion behavior of Zn-Mn-Mg alloys was still lacking in research. It had grown to be a hot research topic to improve the corrosion behavior of Zn alloys by surface treatment to meet the application of degradable Zn alloys in biomedical applications. Micro arc oxidation (MAO) is a simple and effective method to improve the corrosion behavior of the alloy. MAO coatings were suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…With the addition of alloying elements, the microhardness of the alloy is significantly improved, which can meet the requirements of clinical orthopedic implants. This was attributed to that MnZn 13 particles stimulated the recrystallization of Zn grains at room temperature and released the internal stress during the tensile test ( Sun et al, 2021 ). Further alloying 0.1% Li in Zn-Mn alloy introduced finer LiZn 4 second phase, refined the grain, and significantly improved its strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the addition of alloying elements, the microhardness of the alloy is significantly improved, which can meet the requirements of clinical orthopedic implants. This was attributed to that MnZn 13 particles stimulated the recrystallization of Zn grains at room temperature and released the internal stress during the tensile test ( Sun et al, 2021 ). Further alloying 0.1% Li in Zn-Mn alloy introduced finer LiZn 4 second phase, refined the grain, and significantly improved its strength.…”
Section: Discussionmentioning
confidence: 99%
“…Mn is the immune system and a variety of enzymes necessary trace elements play an important role in bone growth and development of animals. Mn deficiency can lead to poor bone growth, reproductive disorders, and neurological disorders ( Sun et al, 2021 ). Li is also necessary for human body nutrition elements, the latest research showed that Li can stimulate the osteogenic differentiation of bone marrow mesenchymal stem cells and promote bone reconstruction ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that the composition and concentration of the electrolyte are crucial parameters for regulating the structure and performance of MAO coatings. These parameters affect the surface morphology, thickness, roughness, and corrosion resistance of MAO coatings [10][11][12]. The choice of the coating agent affects the surface states and properties of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] The ceramic layer has the characteristics of high hardness, strong bonding force with matrix, corrosion resistance, high-temperature oxidation resistance, good insulation, and so on, which is especially suitable for light metal alloy parts that move at high speed and need high wear resistance, corrosion resistance, and high-temperature impact resistance. [22][23][24][25][26][27] However, in the process of micro-arc oxidation, there are often micro-pores, cracks, and other defects, which have adverse effects on the corrosion resistance and wear resistance of micro-arc oxidation film. At present, most of the defects in the process of micro-arc oxidation are investigated by experiments, which will consume a lot of experimental resources and fail to explore the causes of the formation of micropores and cracks from a microscopic perspective.…”
mentioning
confidence: 99%